THE EFFECT OF SALESPERSON ETHICAL BEHAVIOR ON SATISFACTION, TRUST AND CUSTOMER LOYALTY (Study on customers of PT Kawan Lama Sejahtera in Bali) - Wedatama, Putu Bagus (Universitas Pendidikan Indonesia, 2019)
The number of industrial equipment brands on the market has resulted in customers needing the role of sales force to get clear product information and good after-sales service. Sales who can behave ethically will be more trusted and can establish long-term relationships with customers. This study aims to explain the relationship between salesperson ethical behavior towards satisfaction and trust and its effect on customer loyalty levels at PT Kawan Lama Sejahtera at Bali.The population in this study were PT Kawan Lama Sejahtera customers who had made transactions at least 2 times within a period of 1 year. The size of the sampling was determined based on the non probability sampling method, namely purposive sampling with a total sample of 100 respondents. Questionnaire data that are collected from respondents, are analyzed by Structural Equation Modeling (SEM) with AMOS programs.The results of this study indicate that salesperson ethical behavior has a positive and significant effect on customer satisfaction and trust which are a dimension of the quality of the relationship. Customer satisfaction and trust also have a positive and significant influence on customer loyalty. The relationship between salesperson ethical behavior and customer trust is mediated by customer satisfaction, where the effect is significant.The managerial implications of the results of this study can be a consideration in the process of strategic policy making at PT Kawan Lama Sejahtera improve company’s performance in the future. Salesperson need to behave ethically in marketing their products in order to increase customer’s satisfaction and trust, and also establish long-term relationships with customers.